Kebebasan Berpendapat sebagai Pilar Demokrasi dalam Perspektif Hak Asasi Manusia - Astri Meylisa Purba; Nayla Shifa Ananta; Tri Nita Manurung (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Freedom of expression is one of the fundamental rights that serves as the primary foundation of modern democratic systems. This right is not only recognized in international legal instruments such as the International Covenant on Civil and Political Rights (ICCPR) Article 19, but is also explicitly guaranteed in the constitutions of democratic states, including Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia. This study aims to analyze the position of freedom of expression as an essential pillar of democracy within the human rights framework, examine constitutional protection mechanisms and applicable limitations, and evaluate its implementation in the Indonesian legal system. The research method employed is normative legal research with a statute approach, conceptual approach, and comparative approach. The findings indicate that freedom of expression is not merely an individual right, but a collective instrument that enables meaningful public participation in democratic processes. Restrictions on this freedom must fulfill the requirements of legality, necessity, and proportionality as established by the Siracusa Principles. In Indonesia, the primary challenge lies in regulatory plurality that potentially creates overlapping provisions and the risk of criminalizing legitimate expression, particularly through the implementation of the Electronic Information and Transactions Law (UU ITE).